Centimeter‐scale growth of two‐dimensional layered high‐mobility bismuth films by pulsed laser deposition. Issue 1 (28th March 2019) - Yang, Zhibin; Wu, Zehan; Lyu, Yongxin; Hao, Jianhua
Abstract: Ever since discovery of graphene, two‐dimensional (2D) materials become a new tool box for information technology. Among the 2D family, ultrathin bismuth (Bi) has attracted a great deal of attention in recent years due to its unique topological insulating properties and large magnetoresistance. However, the scalable synthesis of layered Bi ultrathin films is rarely been reported, which would greatly restrict further fundamental investigation and practical device development. Here, we demonstrate the direct growth of homogeneous and centimeter‐scale layered Bi films by pulsed laser deposition (PLD) technique. The as‐grown Bi film exhibits high‐purity phase and good crystallinity. In addition, both (111) and (110)‐oriented Bi films can be synthesized by precisely controlling the processing temperature. The characterization of optical properties shows a thickness dependent band gaps (0.075‐0.2 eV). Moreover, Bi thin‐film‐based field‐effect transistors have been demonstrated, exhibiting a large carrier mobility of 220 cm 2 V −1 s −1 . Our work suggests that the PLD‐grown Bi films would hold the potential to develop spintronic applications, electronic and optoelectronic devices used for information science and technology. Abstract : Centimeter‐scale two‐dimensional (2D) layered bismuth (Bi) films are deposited by pulsed laser deposition (PLD). Both (111) and (110) orientations have been obtained by accurately controlling the fabrication conditions. Thickness dependence of the band gaps (0.075‐0.2 eV) is observed and high mobility Bi field‐effect transistors (FETs) are demonstrated. This work suggests that the PLD grown Bi film is a potential candidate for future optoelectronic applications in 2D limit.